2017
DOI: 10.1111/evj.12702
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histopathological features of myofibrillar myopathy in Warmblood horses

Abstract: Summary Background To report a novel exertional myopathy, myofibrillar myopathy (MFM) in Warmblood (WB) horses. Objectives To 1) describe the distinctive clinical and myopathic features of MFM in Warmblood horses and 2) investigate the potential inheritance of MFM in a Warmblood family. Study design Retrospective selection of MFM cases and prospective evaluation of a Warmblood family. Methods Retrospectively, muscle biopsies were selected from Warmblood horses diagnosed with MFM and clinical histories o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 30 publications
3
46
0
Order By: Relevance
“…Lower tropomyosin (↓3.2 log 2 fold MFM) content in MFM muscle could be the result of protein oxidation or alternatively, could reflect a primary underlying disorder (30, 35, 36). Decreased tropomyosin content is known to occur in limb girdle muscular dystrophy 2A and hereditary inclusion body myositis (24), (55), which have different histopathologic appearances compared with MFM in horses (63, 64). Mutations in the Z-disc protein MYOZ2 can cause myofibrillar disarray and hypertrophic cardiomyopathy and gene expression of MYOZ2 was significantly decreased in resting MFM vs. control horses (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower tropomyosin (↓3.2 log 2 fold MFM) content in MFM muscle could be the result of protein oxidation or alternatively, could reflect a primary underlying disorder (30, 35, 36). Decreased tropomyosin content is known to occur in limb girdle muscular dystrophy 2A and hereditary inclusion body myositis (24), (55), which have different histopathologic appearances compared with MFM in horses (63, 64). Mutations in the Z-disc protein MYOZ2 can cause myofibrillar disarray and hypertrophic cardiomyopathy and gene expression of MYOZ2 was significantly decreased in resting MFM vs. control horses (45).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry was used to investigate desmin aggregation, regeneration, and myosin isoforms that had altered gene expression as well as peptide expression in the proteomic profile. Staining was performed for desmin (1:100 anti-desmin-mouse monoclonal D33; Agilent Technologies, Santa Clara CA) and MHCd (1:50 mouse monoclonal anti-MHCd; Leica Biosystems, Buffalo Grove, IL) as previously described (63, 64). For MYH13 staining, flash-frozen muscle samples 7 μm thick were placed on charged slides and air-dried overnight at 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…A diagnosis of myofibrillar myopathy (MFM) in Arabian and Warmblood horses (WB) is based on histological features that overlap with human MFM, including desmin aggregates and myofibrillar disarray in skeletal muscle fibres 1,2 . Clinical signs associated with MFM WB are usually apparent by 11 years of age and include exercise intolerance, a reluctance to move forward under saddle and a mild lameness not attributable to an underlying orthopaedic cause 1–3 . In humans, clinical signs of MFM are often apparent after the 4th decade of life 4–8 and include progressive muscle atrophy and the potential for respiratory compromise, cardiomyopathy and death 4,5,9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…In humans, clinical signs of MFM are often apparent after the 4th decade of life 4–8 and include progressive muscle atrophy and the potential for respiratory compromise, cardiomyopathy and death 4,5,9,10 . Cardiac impairment, the severity and progression of muscle atrophy as well as the extent of ectopic protein aggregation appear to be more marked in human patients with MFM than MFM‐affected WB 1,11,12 …”
Section: Introductionmentioning
confidence: 99%
“…Myofibrillar myopathy has been described in endurance horses (mostly Arabian and Arabian crosses) with intermittent signs of muscle pain and stiffness after exercise 18 . The same authors reported myofibrillar myopathy in a group of Warmblood horses showing exercise intolerance, reluctance to go forward, stiffness and poorly localised lameness 19 . In most horses muscle biopsy was performed due to inconclusive diagnostic anaesthesia.…”
mentioning
confidence: 99%